Origin and distribution of the BRCA2-8765delAG mutation in breast cancer - Palomba, Grazia (BioMed Central, 2007)
BACKGROUND: The BRCA2-8765delAG mutation was firstly described in breast cancer families from French-Canadian and Jewish-Yemenite populations; it was then reported as a founder mutation in Sardinian families. We evaluated both the prevalence of the BRCA2-8765delAG variant in Sardinia and the putative existence of a common ancestral origin through a haplotype analysis of breast cancer family members carrying such a mutation. METHODS: Eight polymorphic microsatellite markers (D13S1250, centromeric, to D13S267, telomeric) spanning the BRCA2 gene locus were used for the haplotype analysis. Screening for the 8765delAG mutation was performed by PCR-based amplification of BRCA2-exon 20, followed by automated sequencing. RESULTS: Among families with high recurrence of breast cancer (≥ 3 cases in first-degree relatives), those from North Sardinia shared the same haplotype whereas the families from French Canadian and Jewish-Yemenite populations presented distinct genetic assets at the BRCA2 locus. Screening for the BRCA2-8765delAG variant among unselected and consecutively-collected breast cancer patients originating from the entire Sardinia revealed that such a mutation is present in the northern part of the island only [9/648 (1.4%) among cases from North Sardinia versus 0/493 among cases from South Sardinia]. CONCLUSION: The BRCA2-8765delAG has an independent origin in geographically and ethnically distinct populations, acting as a founder mutation in North but not in South Sardinia. Since BRCA2-8765delAG occurs within a triplet repeat sequence of AGAGAG, our study further confirmed the existence of a mutational hot-spot at this genomic position (additional genetic factors within each single population might be involved in generating such a mutation).